536 CHANGES IN MYOCARDIAL BIOMARKERS TO DIFFERENTIATE TYPE 2 MYOCARDIAL INFARCTION FROM TYPE 1 MYOCARDIAL INFARCTION AND ACUTE MYOCARDIAL INJURY: A PROSPECTIVE COMPARISON STUDY. (15th December 2022) - Mautone, Francesco; Mele, Marco; Ragnatela, Ilaria; D´alessandro, Damiano; Rossi, Luciano Umberto; Diomede, Nicolangelo; Diomede, Davide; Giannetti, Laura; Palmieri, Gianpaolo; Corbo, Maria Delia; Vitale, Enrica; Brunetti, Natale Daniele
Abstract: Background: According to 4 th Universal Definition of Myocardial Infarction (MI), it is possible to differentiate clinically type 2 MI (T2MI) from type 1 MI (T1MI) and acute myocardial injury (AMI). However, in many cases this differentiation may be difficult. To date there are poor data that allow to distinguish AMI, T2MI and T1MI from the changes and the absolute or relative values of biomarkers of myocardial necrosis. We sought to compare T2MI vs T1MI and vs AMI in terms of cardiac biomarkers changes. Methods: we consecutively enrolled 90 patients (30 with T1MI, 30 with T2MI and 30 with AMI). excluding patients with ST-segment elevation myocardial infarction. The ratio of the peak to the upper limit of normal (RULN) were calculated for both CK-MB and cardiac troponin T (cTnT). Moreover, the ratio of peak cTnT to peak CK-MB was also calculated. Results: the ratio peak/RULN for cTnI and CK-MB were significantly higher for T1MI in comparison with T2MI (cTnI 100.8 vs 67.1, p < 0.001; CK-MB 2.1 vs 0.66, p 0.003) while there were not significant differences between T2MI and AMI (T2MI 67.1 vs AMI 47.3., p 0.159; T2MI 0.66 vs AMI 0.39, p 0.052). Interstingly, there was a higher rise of cTnT than CK-MB in type 2 compared with type 1 myocardial infarction, so that the ratio of peak cTnT to peak CK-MB was significantly higher for T1MI in comparison with T2MI (T1MI 196.2 vs AMI 20.5, p 0.008). Conclusions: Both cTnT and CK-MB peaks were higher in T1MI than in T2MI. Furthermore, cTnT rises out of proportion to CK-MB in T2MI. These changes may contribute to a better differentiation between T2MI and T1MI.